Enabling mechanisms in business venturing of maritime autonomous technologies - Riksheim, Kristian Listou; Strand, Øivind; Alsos, Ole Andreas (Journal of physics. Conference series, 2025)
Enabling factors for the commercialization of maritime autonomous technologies (MAT) have previously been identified in the literature: Digitalization, environmental requirements, changes in regulations and crew shortage, amongst others. We utilize a recently developed theoretical framework, the External Enabler Framework (EEF) from Per Davidsson, for clarifying enabling factors, enabling mechanisms, and their characteristics, and how they affect business venturing related to MAT. This paper relates to the Norwegian capacity-building project MIDAS, funded by the Norwegian Research Council. The data is from a survey with a hundred respondents from the Norwegian maritime industries, conducted in September 2023. When comparing the EEF framework with our survey data, we identify four out of eight enabling factors and three out of nine mechanisms to be relevant for MAT. Comments are given on the applicability of EEF to such a complex industry sector as the maritime sector.